Life cycle assessment of ocean liming for carbon dioxide removal from the atmosphere. (10th October 2022) - Foteinis, Spyros; Andresen, John; Campo, Francesco; Caserini, Stefano; Renforth, Phil
Abstract: The world's oceans are an important part of the global carbon cycle, having already absorbed one-quarter of the anthropogenic carbon emissions, however, at the expense of surface ocean acidity, which has increased around 30% since the Industrial Revolution, affecting marine ecosystems. Ocean liming, whereby particulate calcium oxide or, more likely, hydroxide is spread to surface ocean waters can address, at least partly, both the need for carbon dioxide removal (CDR) and ocean acidification. While the idea was proposed almost three decades ago, previous studies have focused on techno-economic feasibility but not on environmental sustainability. Life cycle assessment revealed that limestone calcination is the main environmental hotspot followed by the capture and storage of the calcination CO2 emissions. Mining, comminution, and hydration had a small impact, while results were sensitive to the kiln technology, fuel type, electricity mix, and transportation. Differences between the carbon and environmental footprint highlight that multi-issue life cycle impact assessment methods may be more appropriate when assessing CDR rather than only using carbon balances. Clean and energy efficient kilns (e.g., solar calciners) and the use of renewable energy optimize the system's environmental performance (total carbon and environmental footprint −1031 kgCO2 eq and −15.1 Pt per ton of lime spread in the ocean, respectively). The valorisation of the CO2 emissions from limestone calcination, e.g., for fuels, chemicals, or plastics production, could potentially further improve ocean liming's environmental profile, through avoided emissions, however net removal would depend on the longevity of the use. Results imply that CO2 removal at the Gt yr. −1 scale can be achieved, however more research is required on the biological and ecological implications of this CDR approach. Highlights: Ocean liming's environmental performance was examined using LCA. Environmental hotspots include calcination heat and electricity consumption. CCS or CCU during calcination is required. Sensitivity analysis revealed future environmentally sustainable systems. At optimum conditions 1034 kg CO2 tCaO −1 can be removed/avoided.